Ritual dan Mistisisme dalam Tradisi Pernikahan Suku Tengger: Dari Perjodohan hingga Pembagian Warisan - Susanti, Anik; Sabariman, Hoiril (Sosial Budaya, 2022)
Tengger ethnic group have unique customs in the wedding tradition. They maintain the mores of wedding in the form of rituals and mysticism from generation to generation. The purpose of this study is to analyze and explain the rituals and mysticism that exist in the Tengger tradition of wedding. Descriptive qualitative methods are used to scuttle the phenomenon. Informants are determined based on criteria and considerations to have a thorough understanding of rituals and mysticism in the wedding tradition. Data is collected through interviews, observations, and supporting documentation. The results of this study found that there are rituals performed by the community in the wedding tradition. Starting from the affairs of matchmaking, the parents in Tengger are also guided by a Primbon that is understood by some people including shamans. After the matchmaking, a meeting of friends is the day that the groom meets the bride-to-be. Then held a traditional Walagara (wologoro) ceremony consisting of japa mantra and banten kayoban.  Japa mantra is summoning the spirits of ancestors, ancestral spirits, and spirit guards of the village. Banten kayoban is a family inner bond between men and women after wedding. If the custom is not implemented, the marriage carried out is considered invalid even though it is carried out according to the State, even getting social sanctions in the Tengger community. The division of inheritance rights is owned by parents, an equal division between boys and girls. Mysticism is found in almost every ritual in the wedding tradition. Tengger people believe that mystical elements have a power that brings good to couples who want to get married.